Trajectory plots that highlight statistically different periods among multiple foods studied using the temporal dominance of sensations method - Natsume, Hiroharu; Okamoto, Shogo; Nagano, Hikaru (Food Science and Technology Research, 2024)
The temporal dominance of sensations (TDS) method allows us to record temporal changes in multiple sensations during an experience, such as eating food. A trajectory plot is used to visualize the experimental results of the TDS method and is useful for comprehending multidimensional sensory transitions in a low-dimensional principal component space. Castura et al. (2023) proposed an approach to statistically compare multiple food products in such spaces. We rectify the hypothesis-testing method of that approach and modify the visualization method, such that the periods in which the products are statistically different from each other are easily recognized. The developed method helps us understand when and how a food product feels different from others during the eating experience and can contribute to designing new products by focusing on their time-series experience.